Rising damp in historical buildings: a serious building pathology - M. I. TORRES (2006)
The study of the restoration of historical buildings is becoming increasingly important, both because of the need to encourage the conservation of architectural heritage, and because of a heightening awareness that this activty is very interesting for planners, builders and researchers. This means that the number of scientific studies involving pathology and restoration is also growing. If we analyze the pathologies observed in historic buildings systematically, we find that rising damp is a serious problem. The purpose of this paper is to systematize the problems caused by rising damp in historic buildings and the techniques for treating them. At the same time, it confronts the problems that still face us today in terms of dealing with rising damp with research that has been developed in an effort to minimize these problems. KEYWORDS: Rising damp, historical buildings, building pathology